The Effect Of Corporate Risk Disclosure (CRD) and Good Corporate Governance (GCG) On The Value Of Banking Companies Listed On The Indonesia Stock Exchange - Feby Nurul Adzkia; Imanuriea Annisa Putri (International Journal of Economics, Business and Innovation Research, 2026)
This study aims to examine the effect of Corporate Risk Disclosure (CRD) and Good Corporate Governance (GCG) on firm value of banking companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Firm value is measured using Tobin’s Q, while CRD is measured through a risk disclosure index. GCG is proxied by independent commissioners, audit committees, and institutional ownership. This research employs a quantitative approach with explanatory research design. The sample consists of 23 banking firms selected through purposive sampling, resulting in 69 observations. Data analysis is conducted using multiple linear regression. The results indicate that Corporate Risk Disclosure has a positive and significant effect on firm value. Furthermore, Good Corporate Governance mechanisms also have a positive and significant effect on firm value. These findings suggest that transparency in risk disclosure and the implementation of good corporate governance enhance investor confidence and firm value in the banking sector.